Semi-adaptive switching control for infusion of two interacting medications. (May 2018) - Jin, Xin; Hahn, Jin-Oh
Highlights: A semi-adaptive switching control approach to two medication infusions was studied. It accounts for regime-dependent inter-medication synergy on clinical responses. It adapts control parameters online by making use of dose-response measurements. It boasts adequate set point tracking and parameter estimation performance. Abstract: In this paper, a semi-adaptive switching control approach to the infusion of two interacting medications was investigated. A two-mode switching control technique was developed based on two-input two-output dose-response models associated with two distinct operating regimes, where the dose-response model associated with each mode was obtained by linearizing a nonlinear two-input two-output dose-response model near an operating point in the neighborhood of which one medication is used as primary therapy while the other is used as secondary therapy. The controller associated with each mode was designed based on a semi-adaptive control technique, where a subset of high-sensitivity model parameters are adapted in real time while the remaining low-sensitivity parameters are fixed at relevant nominal values. In this way, the controller can account for the therapeutic regime-dependent influence of medications and inter-medication synergy on clinical responses, while making use of dose-response measurements for online adaptation of dose-response models. The proposed approach was applied to an example scenario in which cardiac output and respiratory rate are regulated via the infusion of propofol and remifentanil in an in-silico simulation setting. The results illustrated that the semi-adaptive switching control approach could provide benefits in terms of reference tracking performance and parameter estimation accuracy.